2019
DOI: 10.21608/puj.2019.15158.1050
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic characterization of human Cryptosporidium isolates and their respective demographic, environmental and clinical manifestations in Egyptian diarrheic patients

Abstract: Cryptosporidium is a worldwide enteric zoonotic protozoan parasite infecting a broad range of hosts, including humans, ruminants, birds, reptiles and fish [1,2]. It is the main cause of diarrheal illness in both developed and developing countries [3]. Cryptosporidiosis can result in severe diarrhea, which is usually self-limited in immunocompetent individuals, but may be chronic and life-threatening in immunocompromised patients [4]. It was estimated that up to 10% of cryptosporidiosis occurred between one to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…A previous study by El-Hamshary et al [40] certified that the modified Zeihl Neelsen stain provided a lower sensitivity and specificity of 55.3% and 79%. On the other hand, El-Missiry et al [41] recorded 100% sensitivity, specificity, and accuracy of the stain. It is worth mentioning that one sample was positive by microscopy but negative with nPCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by El-Hamshary et al [40] certified that the modified Zeihl Neelsen stain provided a lower sensitivity and specificity of 55.3% and 79%. On the other hand, El-Missiry et al [41] recorded 100% sensitivity, specificity, and accuracy of the stain. It is worth mentioning that one sample was positive by microscopy but negative with nPCR.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Zaglool et al [46] reported that ICT sensitivity was 86.7% and specificity was 100%, when compared to staining. Controversially, El-Missiry et al [41] recorded that ICT was 65% sensitive, 48% specific, with 50% accuracy inpatients of different ages: 214 patients ≤ 5 years, 136 ≥ 5 years; of both sexes, and different immune status. Moreover, El-Settawy and Fathy [47] recorded that ELISA was sensitive (85.7%) and specific (100%) with 96.5% accuracy in diagnosis of cryptosporidiosis compared with nPCR.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme immunoassay (EIA) methods have many advantages as they are faster, easy to perform, inexpensive, and more sensitive compared to the immunofluorescence methods [33]. Rapid immunochromatographic (strip) tests can also be used [158,159] as they are used for the detection of the oocyst cell wall proteins using monoclonal antibodies [160].…”
Section: Diagnosis Of Cryptosporidiummentioning
confidence: 99%